Clerodane type diterpene as a novel antifungal agent from polyalthia longifolia var. pendula - Bhattacharya, Asish K.; Chand, Hemender R.; John, Jyothis; Deshpande, Mukund V. (European Journal of Medicinal Chemistry, 2015)
Bioactivity-guided chemical examination of methanolic extract of leaves of Polyalthia longifolia var. pendula led to the isolation of the active constituent, a diterpene 1 which was identified as 16α-hydroxycleroda-3,13(14)Z-dien-15,16-olide on the basis of its spectral data. Among the tested strains, diterpene 1 was found to exhibit antifungal activities having MIC90 values of 50.3, 100.6 and 201.2 μM against Candida albicans NCIM3557, Cryptococcus neoformans NCIM3542 (human pathogens) and Neurospora crassa NCIM870 (saprophyte), respectively. Initial, structure–activity-relationship (SAR) data generated by synthesizing some derivatives revealed that the double bond between C3–C4 and the free hydroxyl group at C16 are crucial for the antifungal activity of the diterpene 1. The mode of action of 1 in C. albicans is due to compromised cell membrane permeability and also probably due to disruption of cell wall structures. The red blood cell haemolysis of all the compounds (1–4) did not show any significant haemolysis and was found to be less than 15% for all the compounds when tested at highest concentration, i.e. 1200 μM. Interestingly, all the tested compounds inhibited Y–H transition in dimorphic C. albicans NCIM3557 at much lower concentration than their MIC90 values. Determination of ROS generation by diterpene 1 using DCFH-DA and DHR123 (dihydrorhodamine) staining of C. albicans NCIM3557 indicated production of intracellular ROS as a mechanism of antifungal activity.
Keywords: Diterpene; Polyalthia longifolia; Isolation; Flash chromatography; Natural products; Antifungal activity